2019
DOI: 10.1155/2019/1372138
|View full text |Cite
|
Sign up to set email alerts
|

Different Therapeutic Effects of Transcranial Direct Current Stimulation on Upper and Lower Limb Recovery of Stroke Patients with Motor Dysfunction: A Meta-Analysis

Abstract: Objective To explore the effects of transcranial direct current stimulation (tDCS) on the motor recovery of stroke patients and the effect differences between the upper limb and lower limb. Methods Randomized control trials published until January 2019 were searched from PubMed, Embase, ScienceDirect, and Cochrane Library databases. The standardized mean difference (SMD) with 95% confidence interval (CI) was estimated separately for upper and lower limb motor outcomes to understand the mean effect size. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 50 publications
2
61
3
1
Order By: Relevance
“…The major inding of this study was that anodal tDCS with OGWT results to greater clinical improvement in mobility function and QoL than cathodal tDCS with OGWT and OGWT alone. Transcranial direct current stimulation has been shown to improve force generation, motor control and joint coordination in lower limb leading to improve functional mobility while OGWT has also been shown to promote functional mobility among stroke survivors [17,18,20,21]. An, et al [7] in a study titled effect of tDCS of stroke patients on depression and quality of life reported improvement in QoL of stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major inding of this study was that anodal tDCS with OGWT results to greater clinical improvement in mobility function and QoL than cathodal tDCS with OGWT and OGWT alone. Transcranial direct current stimulation has been shown to improve force generation, motor control and joint coordination in lower limb leading to improve functional mobility while OGWT has also been shown to promote functional mobility among stroke survivors [17,18,20,21]. An, et al [7] in a study titled effect of tDCS of stroke patients on depression and quality of life reported improvement in QoL of stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
“…The main effect of tDCS on the brain is modulation of the resting membrane potentials, tDCS can cause either neuronal membrane depolarization (long term potentiation) or hyperpolarization (long term depression) depending on the type of electrode placement resulting in different type of stimulation while the main effect of OGWT on the brain and lower limb is motor learning, control and skill which translate to functional mobility and improve QoL [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In this technique, direct current applied by electrodes located on the scalp modifies the activity of both cortical (Nitsche & Paulus, 2000) F I G U R E 3 Schematic diagram of the experimental designs to investigate short-term (a), persistent, long-lasting (b) effects of acute tsDCS, and adaptive changes in response to chronic tsDCS application (c) in rat MNs a b c and subcortical regions. Therapeutic benefits of tDCS have recently been reported in motor rehabilitation (Bai et al, 2019), pain management (Ramger et al, 2019) and even psychiatric disorders (Kuo et al, 2017). tsDCS was introduced by Cogiamanian et al (2008) to induce long-lasting alterations of the conduction velocity in the human lemniscal pathway.…”
Section: Translational Implications Of Direct Current Stimulationmentioning
confidence: 99%
“…There are previous reports on the use of tDCS in alleviating neurologic disorders, including stroke ( 4, 15 ). Meta-analyses of published reports ( 16, 17 ) have shown a large variability in the clinical efficacy of tDCS that may be attributed to differences in the tDCS protocol and stroke condition. We thus examined the effect of tDCS on motor learning in a relatively defined mouse model of stroke.…”
mentioning
confidence: 99%
“…The timing of tDCS relative to the targeted task performance has been addressed in previous studies of healthy human subjects and stroke patients, but conflicting results have been reported, as summarized by various meta-analyses ( 16, 17 ). For examples, online but not offline anodal tDCS of M1 during motor sequence task was found to enhance motor learning, while online cathodal tDCS had no or opposite effects ( 18, 19 ).…”
mentioning
confidence: 99%